Pengaruh Penambahan Bawang Putih Terhadap Kualitas Telur Asin - Kurnia, Nina; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
Improved quality of salted egg conducted by creating a new variant, one of which with the addition of garlic. This research aims to analyze the effect of the addition of garlic as much as 0%, 15%, 30% and 45% of the quality colour, aroma, texture, and taste the salty eggs. Type of research is true experimental with completely randomized design method. Variables used are variable X (garlic) and the variable Y (quality of salted eggs). The data used was obtained directly from 30 semi trained panelists. Data analyzed by using ANAVA, if different real continued with Test Duncan. The results showed there is the influence of the addition of garlic to the quality of the scent is not fishy, garlic aroma, taste salty, savory taste, aroma and taste of the hedonic. There is no real influence on quality of the color orange, white eggs on a chewy texture, granulated texture in egg yolk, hedonic color and texture of salted egg hedonic. The quality of salted eggs best use garlic as much as 45% (X3).Keywords: Garlic, Quality of Organoleptic, Salted Eggs.